Estimation Of Changes in Water Quality Parameters in Rawa Pening Lake Based on Remote Sensing Data - Fariz, Trida Ridho; Amalia, Andin Vita; Jabbar, Abdul; Atunnisa, Rifa’ (Universitas Negeri Semarang, 2024)
Lake Rawa Pening, in Indonesia, is one of the super lakes of revitalization priority. The factor that causes Lake Rawa Pening to become a priority lake is high sedimentation, which is triggered by the expansion of land cover such as settlement, agriculture, and industry in the Rawa Pening Catchment Area. This study examines changes in water quality parameters in Rawa Pening Lake from remote sensing data with Google Earth Engine (GEE). The physical parameters used to assess water quality are the concentration of Total Suspended Solid (TSS) and the area of water vegetation (water hyacinth). The results indicate that the water quality of Rawa lake has changed in the TSS level and the distribution area of aquatic vegetation. In general, from 2017, 2019 and 2021 there were fluctuations in the percentage of water hyacinth and TSS. Modeling results indicate that Lake Rawa Pening is mostly hypereutrophic.